Pengaruh Audit Delay, Audit tenure, Dan Opini Audit Terhadap Auditor Switching Dengan Financial Distress Sebagai Variabel Moderating - Fenny Chikita Rizky; Karya Satya Azhar; Yani Suryani (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the effect of audit delay, audit tenure and audit opinion on auditor switching with financial distress as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The type of research used in this study is associative with a quantitative approach method. The population in this study were 195 companies, the sampling method used was purposive sample, with a total sample of 46 companies. The data analysis technique used is logistic regression analysis with statistical data processing using SPSS version 20.0 data processing application. The results of this study indicate that audit delay has no effect on auditor switching, audit tenure has been shown to have a positive and significant effect on auditor switching and audit opinion has no effect on auditor switching. Financial distress is not able to moderate the relationship between the effect of audit delay, audit tenure, and audit opinion on auditor switching in manufacturing companies listed on the Indonesia Stock Exchange (IDX).